2023
DOI: 10.1101/2023.09.21.23295919
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Anti-SARS-CoV-2 Antibody Levels Associated with COVID-19 Protection in Outpatients Tested for SARS-CoV-2, US Flu VE Network, October 2021–June 2022

Kelsey M. Sumner,
Ruchi Yadav,
Emma K. Noble
et al.

Abstract: Background: We assessed the association between antibody concentration within 5 days of symptom onset and COVID-19 illness among patients enrolled in a test-negative study. Methods: From October 2021 to June 2022, study sites in seven states enrolled and tested respiratory specimens from patients of all ages presenting with acute respiratory illness for SARS-CoV-2 infection using rRT-PCR. In blood specimens, we measured concentration of anti-SARS-CoV-2 antibodies against the ancestral strain spike protein rece… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Against pre-Omicron variants, virus neutralization titers and IgG antibody concentrations were associated with protection; however, antibody binding and neutralization activity was lower against Omicron variants [2,8,18]. In addition, anti-N bAb seropositivity cut-off values were based on mean fluorescence intensity using serum standards rather than blood spots [10,13]. All case patients included in this study had mild illness; baseline antibody levels and immune responses may differ among patients with severe or prolonged SARS-CoV-2 infection [19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Against pre-Omicron variants, virus neutralization titers and IgG antibody concentrations were associated with protection; however, antibody binding and neutralization activity was lower against Omicron variants [2,8,18]. In addition, anti-N bAb seropositivity cut-off values were based on mean fluorescence intensity using serum standards rather than blood spots [10,13]. All case patients included in this study had mild illness; baseline antibody levels and immune responses may differ among patients with severe or prolonged SARS-CoV-2 infection [19].…”
Section: Discussionmentioning
confidence: 99%
“…Between December 2021 and June 2022, respiratory swabs and acute-phase dried blood spots on filter paper were obtained <5 days after symptom onset from ambulatory patients with respiratory illness enrolled in the US Influenza Vaccine Effectiveness Network, as previously described [9,10]. Patients who tested positive for SARS-CoV-2 by nucleic acid amplification in respiratory specimens were scheduled for convalescent-phase blood sample collection at 21-56 days after enrollment.…”
Section: Study Population and Sample Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using DBS specimens collected during acute illness from patients with laboratory‐confirmed COVID‐19 and non‐COVID‐19 illnesses, we previously showed that anti‐N antibody seropositivity modified COVID‐19 mRNA vaccine effectiveness against symptomatic SARS‐CoV‐2 infection with SARS‐CoV‐2 Delta and Omicron variants [12]. Among acutely ill patients, higher levels of binding antibodies against ancestral S protein reduced the odds of testing positive for SARS‐CoV‐2 Delta and Omicron variants [13]. Here, we assessed humoral immune response to SARS‐CoV‐2 infection comparing acute‐ and convalescent‐phase IgG antibody levels against N and ancestral S RBD antigens among case patients infected during Omicron variant–predominant periods from December 2021 through June 2022.…”
Section: Introductionmentioning
confidence: 99%
“…Respiratory swabs and acute‐phase DBS were obtained < 5 days after symptom onset from ambulatory patients with respiratory illness enrolled in the US Influenza Vaccine Effectiveness Network [12, 13]. Previous analysis demonstrated no increase in mean anti‐N antibody concentration from DBS collected < 5 days after symptom onset among SARS‐CoV‐2‐infected patients [13].…”
Section: Introductionmentioning
confidence: 99%